QODARIYAH DALAM SOROTAN HADIS - Agusman Damanik (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
Qodariyah is synonymous with one of the streams in the science of kalam which holds that humans determine qadar as a behavior, both good and bad. Historically on the theological dimension, Qodariyah was the flow that was first raised by Ma 'bad Aljuhaini ghulam Dimasqy. Qadariyah comes from Arabic, namely qadara which means ability and strength. The terminology / term is a school that believes that all human actions are not intervened by God. Imam Nawawi said, " O my brothers and sisters, may Allah give us all instructions - see how perfect the gentleman of Allah, Azza Wa Jalla! Reflect on these sentences. His word : عنده (on his side) hints at God's attention to servants' deeds. Word: كاملة (perfect) serves as a confirmation and shows God's great attention to it. Then he sallallaahu 'alaihi wasallam said about evil which was intended by a servant but he left : كتبها الله عنده حسنة كاملة (So God records it as a perfect good). He mengutannya with the word "we" (perfect). Whereas if he continues to do that evil, then Allah records it as an ugliness. Here the small amount of balsan is strengthened with the word "wahidah" (one) not with kat "we".Qodariyah, qadr, hadith, Islam